HUKUM KETERLIBATAN PEREMPUAN DALAM RANAH PUBLIK: Kajian Tafsir Tekstual dan Kontekstual - Musolli Musolli (Prodi Hukum Keluarga Fakultas Agama Islam Universitas Nurul Jadid, 2020)
The involvement of women in the public sphere should be accompanied by two theories, textual and contextual. These two theories appear to support a big agreement that the Koran is present in addition to being a solution but also providing innovation. The innovation offered is the concept that the Koran is suitable for every situation.Keywords: women, Koran, textual and contextual.